Genome-Wide Identification and Characterization of PRR Gene Family and their Diurnal Rhythmic Expression Profile in Maize - Cuiling Wang; Leili Wang; Qingqing Liu; Yanling Zhang; Keqing Dong (International Journal of Genomics)
As essential components of the circadian clock, the pseudo-response regulator (PRR) gene family plays critical roles in plant photoperiod pathway. In this study, we performed a genome-wide identification and a systematic analysis of the PRR gene family in maize. Nine ZmPRRs were identified, and the gene structure, conserved motif, evolution relationship, and expression pattern of ZmPRRs were analyzed comprehensively. Phylogenetic analysis indicated that the nine ZmPRR genes were divided into three groups, except for ZmPRR73, two of which were highly homologous to each of the AtPRR or OsPRR quintet members. Promoter cis-element analysis of ZmPRRs demonstrated that they might be involved in multiple signaling transduction pathways, such as light response, biological or abiotic stress response, and hormone response. qRT-PCR analysis revealed that the levels of ZmPRRs transcripts varied considerably and exhibited a diurnal rhythmic oscillation expression pattern in the given 24-h period under both SD and LD conditions, which indicated that the level of transcription of ZmPRRs expression is subjected to a circadian rhythm and modulated by light and the circadian clock. The present study will provide an insight into further exploring the biological function and regulatory mechanism of ZmPRR genes in circadian rhythm and response to photoperiod in maize.